Development of a duplex real-time PCR method for the detection of influenza C and D viruses - Letian Zhang; Meng Lu; Jiaxuan Lu; Ningning Wang; Zhongzhou Pan; Shuo Su (BMC, 2021)
Abstract Influenza viruses are major respiratory pathogens known to infect human and a variety of animals and are widely prevalent worldwide. Genome structure of influenza D virus (IDV) is identical to that of influenza C virus (ICV), and phylogenetic analyses suggest that IDV and ICV share a common ancestry and high homology. To date, the prevalence of ICV and IDV in China is unclear, but these viruses represent a potential threat to public health due to cross-species transmission and zoonotic potential. To efficiently monitor ICV and IDV, it is necessary to establish a dual detection method to understand their prevalence and conduct in-depth research. A duplex real-time PCR method for the simultaneous detection of ICV and IDV was developed. TaqMan fluorescent probes and specific primers targeting NP gene of ICV and PB1 gene of IDV were designed. This method exhibited good specificity and sensitivity, and the detection limit reached 1 × 101 copies/μL of plasmid standards of each pathogen. Thirty-one clinical swine samples and 10 clinical cattle samples were analyzed using this method. One positive sample of IDV was detected, and the accuracy of clinical test results was verified by conventional PCR and DNA sequencing. The duplex real-time PCR detection method represents a sensitive and specific tool to detect ICV and IDV. It provides technical support for virus research and clinical diagnosis of ICV and IDV. This information will benefit animal and human health.